PENGARUH GAYA KEPEMIMPINAN, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada PT. Pos Indonesia Cabang Kota Semarang ) - Elfrida Dwi Ana Listyani, 15.05.51.0069; Murdiyanto, Agus (Students' Journal of Economic and Management, 2019)
This study analyzes leadership style, motivation and work discipline on employee performance. The object of this research in this renewal is the PT.Pos Indonesia branch of Semarang city in this study amounted to 150 employees, samples were calculated by the Slovin formula and the results of 90 respondents. Sampling in this study uses Probability sampling with proportional random sampling. The sample obtained amounted to 60 respondents with a questionnaire (questionnaire) consisting of a list of approvals. After the data is collected, an instrument test is conducted which consists of validity test with factor analysis and reliability test with cronbach alpha. Data analysis in this study used multiple linear regression models with F test and t test. Data processing is done with SPSS 19. The results of the research are: (1) positive and not significant leadership style on employee performance, (2) positive and significant motivation on employee performance. (3) Positive and significant work discipline on employee performance. This research proves the practical and experimental implications.